The Dimensions of Writing in the Media Process - Ali, Azad R.; Mahmood , Azad A. (Mitanni Journal of Humanitarian Sciences, 2020)
The efficient dimensions of writing in the media process (briefly discussed the history of writing, stages, types, bends, and definitions of writing. Then, in the writing process, the chametry and definition of the work, the parties and content of the writing's work have been discussed, and then the characteristics, types, importance and purposes of writing have been discussed. In this research, the format and definition of the example has been discussed and investigated, writing in the media process has been pointed out, the characteristics and phatores of the work writing are at the center of the research and the characteristics of them are mentioned For this purpose, a study was later written in: newspapers, radio and television, the characteristics, principles and goals of each of them have been discussed and evaluated in detail and discussed on a special basis the importance of the author's work and the conditions of this form have been discussed, many hidden aspects have been highlighted and the importance of this type of writer has been highlighted. With the writing box and the media process, two useful horizons are one width. Human beings have built social relations from the perspective of language, and these two horizons have become the source of invention through language and the importance of improving the aspects of life, protecting the rights, principles, principles, social, cultural and religious sources... etc.